Analisis budaya literasi melalui kegiatan samisareng (satu minggu satu kali literasi bareng) terhadap minat baca - Mutia Azizah; Rina Yuliana; Anggi Rahmani (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
Elementary schools play an important role in instilling a culture of literacy. Therefore, schools must be able to create an environment that supports the development of a culture of literacy and increases students' interest in reading. This study aims to describe the planning, implementation, and culture of literacy in relation to reading interest through Samisareng activities. This research was conducted at SDN Serang 3. This study used a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observation, and documentation. The results of this study show that: 1) The planning process for Samisareng activities was carried out systematically by involving all teachers based on needs, taking into account human resources, the provision of facilities and infrastructure, the implementation of Samisareng activities, and the establishment of success indicators; 2) The implementation of Samisareng activities was directly supported by the principal, teachers, staff, and indirectly supported by the students' parents at home; and 3) The form of reading literacy culture through Samisareng activities at SDN Serang 3 has been able to foster students' interest in reading.